Two treatment methods on Ulva prolifera bloom result in distinctively different ecological effects in coastal environment - Dong, Shuhang; Xin, Yu; Liu, Chunying; Xiao, Yanqi; Feng, Xiao; Liu, Tao (Frontiers in Marine Science, 2023)
Green tides Ulva prolifera have broken out in the Yellow Sea for more than 10 years, becoming a periodic ecological disaster. The largest-ever green tide that occurred in 2021 promoted innovation in treatment methods. Different from the traditional harvest-disposal method, a microbial complex formulation was firstly sprayed on the harvest U. prolifera that promotes rapid degradation, and then fermented and disposed into the sea. At present, little was known about the ecological effects of those different treatment methods. In order to examine this hypothesis, we run an in-lab incubation of 60 days to simulate the two methods to degrade U. prolifera, with focuses on the degradation ensued impacts on water quality. The degradation process of fresh U. prolifera over two months was dominated by the continuous and slow release of DOM, and the concentration of DOM in the water column was hardly observed to decrease within two months. The pre-discomposed-disposal method also significantly altered microbial community structure. The pre-decomposing treatment with microbial complex formulations destroyed U. prolifera cell tissues and changed its physical state in seawater from floating to fast depositing, and increased the degradation rate by about 14 times. The rapid decomposition of the released bioactive organic matter consumed a substantial amount of dissolved oxygen in local seawater, which has the potential risk of causing local hypoxia and acidification in a short-term. The pre-decomposition treatment of U. prolifera could be a practical and efficient countermeasures to U. prolifera blooming. After the complete degradation of the pre-decomposed U. prolifera, the resulting dissolved organic matter could increase TA to resist acidification. Overall, compared with traditional harvest-packing-disposal method, the pre-decomposing-disposal treatment is an efficient and environmental-friendly disposal method to deal with the U. prolifera “green tide”, but it should be used cautiously.